Air quality in small and medium wood-based enterprises and health effects amongst exposed population / Murni Amirra Mohd Aminuddin - Mohd Aminuddin, Murni Amirra (2017)
Exposure to air contaminants such as wood dust and volatile organic compounds (VOCs) can cause adverse health effects among the exposed workers. It was found that several personal exposures to total dust exceeded the 5 mg/m3 . Negative relationship (p3 mg/m3 ) with skin irritation.